Factors Affecting Entrepreneurial Decision Making Among University Graduates: A Case Study of Universitas Riau Kepulauan: Faktor-Faktor yang Mempengaruhi Pengambilan Keputusan Berwirausaha di Kalangan Lulusan Perguruan Tinggi: Studi Kasus Universitas Riau Kepulauan - Hati, Ravika Permata; Syafruddin, Syafruddin; Putra, Rizki Eka; Mulyati, Sri; Melania, Sherly (Indonesian Journal of Law and Economics Review, 2023)
This scientific article addresses the concerning issue of increasing unemployment among university graduates in Indonesia, focusing on the Faculty of Economics and Business students at Universitas Riau Kepulauan (class of 2019-2020). Employing a quantitative approach, the research examines the influence of accounting information systems, e-commerce, and income expectations on entrepreneurial decision making. Data from 79 respondents were collected using the Slovin formula and analyzed using SPSS software. The study reveals that the utilization of accounting information systems significantly impacts entrepreneurial decision making, while e-commerce has a positive but non-significant effect. Furthermore, income expectations significantly influence graduates' entrepreneurial choices. The findings underscore the need to foster entrepreneurial mindsets among university graduates to mitigate unemployment challenges. Highlight: The research investigates the concerning increase in unemployment among university graduates in Indonesia, with a focus on the Faculty of Economics and Business students at Universitas Riau Kepulauan. A quantitative approach is employed, using the Slovin formula to gather data from 79 respondents analyzed through SPSS software version 20. The study reveals that the utilization of accounting information systems positively and significantly influences entrepreneurial decision making among the students, while e-commerce shows a positive but non-significant effect, and income expectations significantly impact entrepreneurial choices. Keyword: Unemployment, University Graduates, Entrepreneurship, Accounting Information Systems, E-commerce